2019
DOI: 10.1136/jclinpath-2019-205872
|View full text |Cite
|
Sign up to set email alerts
|

Cytohistological diagnosis of pancreatic serous cystadenoma: a multimodal approach

Abstract: AimsSerous cystadenomata (SCAs) are benign pancreatic cystic neoplasms that present a diagnostic challenge despite many investigational approaches. Notwithstanding the promise of molecular diagnostics, these tests have limited accessibility in day-to-day surgical pathology practices. We aim to corroborate and build on recent evidence which suggests that positive α-inhibin immunohistochemistry (IHC) is a helpful adjunct in the biopsy confirmation of pancreatic SCA. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…The author’s experience that SCAs consistently yield hypocellular EUS-FNAB specimens has also been reported elsewhere 21. Indeed, this contrast with the usually hypercellular specimens from NET is a first way to exclude what the author feels is the closest, most common morphological mimic of SCA.…”
Section: Cystic Lesionsmentioning
confidence: 68%
“…The author’s experience that SCAs consistently yield hypocellular EUS-FNAB specimens has also been reported elsewhere 21. Indeed, this contrast with the usually hypercellular specimens from NET is a first way to exclude what the author feels is the closest, most common morphological mimic of SCA.…”
Section: Cystic Lesionsmentioning
confidence: 68%
“…4,6,9 In one of the latter studies, two of 11 (18%) EUS-FNAB samples reported as morphologically suggestive of SCA still did not show inhibin positivity. 9 Further, in a study where SCA was diagnosed from resected specimens but their pre-operative FNA specimens were more often reported as nondiagnostic or suggesting NET, one of eight (13%) SCAs lacked inhibin expression. 6 Finally, these proportions are similar to the 10% 9 and 18% 8 of resected SCAs reported to lack inhibin positivity.…”
Section: Introductionmentioning
confidence: 89%
“…9 Further, in a study where SCA was diagnosed from resected specimens but their pre-operative FNA specimens were more often reported as nondiagnostic or suggesting NET, one of eight (13%) SCAs lacked inhibin expression. 6 Finally, these proportions are similar to the 10% 9 and 18% 8 of resected SCAs reported to lack inhibin positivity. In a similar fashion to sensitivity, specificity of inhibin as a SCA marker has also been questioned.…”
Section: Introductionmentioning
confidence: 96%
“…[36] SCAs can be identified on the basis of a biochemical profile of carcinoembryonic antigen (CEA) levels <5 ng/mL (sensitivity of 50% and specificity of 95% for SCAs/ pseudocyst) and amylase levels <250 U/L (sensitivity of 44% and specificity of 98% for SCA, mucinous cystadenoma, and mucinous cystadenocarcinoma). [37] Most SCAs (89%-100%) have tumor suppressor gene VHL mutations, including loss of heterozygosity and chromosome 3p aneuploidy. [38] When the cut-off is >5000 pg/mL, elevated levels of vascular endothelial growth factor A (VEGF-A) have a sensitivity of 100% and specificity of 83.7% for differentiating between SCNs and other cystic lesions.…”
Section: Dna Biomarkersmentioning
confidence: 99%
“…[39] Furthermore, expression of a-inhibin on immunohistochemistry has a sensitivity of 80% for identifying SCAs. [37] SPNs SPNs are rare and are often observed in relatively young women (average age <35 years), usually in the pancreatic body and tail. Resected SPNs show a large single tumor (5-10 cm) with cystic and solid components.…”
Section: Dna Biomarkersmentioning
confidence: 99%